Preparation method of nano composite material for adsorbing inert organic matters

By preparing nanocomposite materials, using the combination of quaternary molten salt and carbon-based nanomaterials, the problem of removing inert organic matter in coal chemical high-salt wastewater is solved, and efficient adsorption and cost control are achieved.

CN119386836AInactive Publication Date: 2025-02-07XIAN HENGXU TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411700319.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-02-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The prior art is difficult to effectively remove inert organic matter residues in coal chemical high-salt wastewater, resulting in unsatisfactory treatment effect and high cost.

Method used

A nanocomposite preparation method is adopted to prepare quaternary molten salts, carbon-based crystals and carbon-based nanomaterials, and combine water-soluble phenolic resins and foaming agents to form nanocomposites with high adsorption efficiency.

Benefits of technology

It realizes efficient adsorption of inert organic matter in coal chemical high-salt wastewater, reduces treatment costs, simplifies process flow, and improves the stability of materials and industrial application potential.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005153130280000101
    Figure BDA0005153130280000101
Patent Text Reader

Abstract

The invention discloses a preparation method of a nano composite material for adsorbing inert organic matters, and belongs to the technical field of environment-friendly water treatment. The preparation method comprises the following steps: blending ZnCl2, LiCl, NaCl and KCl in percentage by weight to obtain a solid mixed salt, drying the solid mixed salt, placing the solid mixed salt in a crucible, heating the solid mixed salt until the solid mixed salt is completely molten, cooling and grinding the solid mixed salt to obtain quaternary molten salt; mixing the obtained quaternary molten salt with an intermediate and an organic solvent, putting the mixture into a reaction kettle, carrying out gradient heating crystallization reaction, and washing after the reaction is finished, so as to obtain a carbon-based crystal compound; drying the obtained carbon-based crystallized substance, and roasting in a protective atmosphere to obtain a carbon-based nano material; and mixing the obtained carbon-based nano material with water-soluble phenolic resin and an ethanol solution according to a mass ratio, adding a foaming agent, uniformly stirring to form powder slurry, and granulating to obtain the nano composite material for adsorbing the inert organic matters. The method has the advantages of wide raw material source, short process flow and reasonable and controllable production cost, and can meet the requirements of industrial large-scale preparation; the product stability is high; the adsorption capacity is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of environmental water treatment, and specifically relates to a method for preparing a nano-composite material for adsorbing inert organic matter. The nano-composite material prepared by the method is used to adsorb inert organic matter in chemical high-salt wastewater that has been treated and has zero discharge in the chemical production industry, so as to create conditions for the resource utilization of high-salt wastewater. Background Art

[0002] After the chemical high-salt wastewater passes through the "zero discharge system", concentrated water with a mass fraction of total dissolved solids (TDS) greater than 5% is obtained, which is difficult to biochemically treat. Taking coal chemical industry as an example, the concentrated water is further treated by the salt separation crystallization process to obtain recyclable by-product salts, such as sodium sulfate Na 2 SO 4 and sodium chloride NaCl. The mother liquor produced by the aforementioned salt separation and crystallization process has a salt content of more than 20wt%, and is mixed with inert organic matter such as calcium, magnesium, fluorine, silicon, nitrates and other impurities. At present, the common practice in the coal chemical industry is to evaporate and crystallize the mother liquor to produce miscellaneous salts (i.e. hazardous waste, accounting for 15-20% of the total salt content). The cost of miscellaneous salt disposal is 2,000 to 3,000 yuan / ton, which brings a large economic burden to the owner.

[0003] The inert organic matter remaining in the mother liquor includes more than 40 kinds of substances, including humin, fulvic acid, lutidine, acetophenone, acetone, glutaraldehyde, citric anhydride, chloromethyl thiocyanate and ethylacetamide. Since the inert organic matter is dissolved in high-salt wastewater, it has the characteristics of complex components, small relative molecular weight (generally less than 150Da), high biological toxicity and difficulty in degradation, so it is very difficult to remove it using conventional technology.

[0004] Carbon-based nanomaterials are a type of nanomaterials composed of carbon elements with unique structures and properties. Their dispersed phase scale has at least one dimension of carbon material less than 100nm. On the one hand, nanomaterials have a high surface-to-volume ratio and thus have high chemical activity. On the other hand, taking nanowires as an example, they have a high aspect ratio and there is no constraint on particle transmission in one dimensional direction, which is conducive to technical applications.

[0005] The controllable synthesis, effective assembly, and functional design and performance research of carbon-based nanomaterials have become the premise and guarantee for the practical application of related materials.

[0006] Due to the high salt content of the mother liquor, the existing removal process for the inert organic matter remaining in the mother liquor is mainly based on the "adsorption method", but the effect is not ideal. The mainstream process, such as the combination of "ozone oxidation + activated carbon adsorption", has limited treatment effect, and the removal rate of inert organic matter is only about 30%. The poor regeneration capacity of activated carbon leads to high wastewater treatment costs and expensive treatment fees that are prohibitive. Another example is the combination of "electrochemical oxidation + macroporous resin adsorption", which lacks safety because the mother liquor contains a lot of sodium chloride. After power is turned on, hydrogen (H) is generated at the cathode and anode respectively. 2 ) and chlorine (Cl 2 ), if not separated and collected in time, it will cause chlorine poisoning or even explosion of the mixed gas.

[0007] Activated carbon adsorption technology is relatively simple and the equipment operation is easy to control. The disadvantage is that the adsorption efficiency of activated carbon for inert organic matter is general, far below the theoretical value. Regeneration after adsorption saturation is difficult, resulting in high raw material costs. Moreover, the replaced waste activated carbon is hazardous waste, which is not conducive to environmental protection. Macroporous resin adsorption technology relies on van der Waals forces or the production of hydrogen bonds, also known as molecular forces, which are much weaker than chemical bonds. Therefore, for inert COD (chemical oxygen demand) acted by chemical bonds, the adsorption and separation effect is extremely limited. Moreover, the characteristics of the resin are not suitable for some special environments such as high temperature, high pressure, acid, and alkali.

[0008] The applicant conducted extensive literature searches but did not find any cases of carbon-based nanomaterials being used to adsorb inert organic matter. This may be because the preparation process is relatively complicated, functional design is difficult, and there are problems such as structural instability and poor pore control.

[0009] It can be seen that it is of positive significance to explore the preparation method of carbon-based nanomaterials that can simplify the process, reduce costs, improve efficiency and effectively adsorb inert organic matter in the salt separation crystallization mother liquor. The technical solution to be introduced below was produced in this context. Summary of the invention

[0010] The task of the present invention is to provide a method for preparing a nano-composite material for adsorbing inert organic matter, which method is conducive to avoiding the bottleneck factor restricted by the source of raw materials, is beneficial to simplifying and significantly shortening the process flow, and the preparation cost is controllable to meet the requirements of industrial scale-up preparation, helps to ensure the pore size uniformity of the prepared nano-composite material and has ideal stability and improves the adsorption effect on inert organic matter to create excellent conditions for the resource utilization of high-salt wastewater brine mother liquor.

[0011] The task of the present invention is accomplished by a method for preparing a nanocomposite material for adsorbing inert organic matter, comprising the following steps:

[0012] A). Prepare quaternary molten salt. First, ZnCl 2 , LiCl, NaCl and KCl are mixed according to weight percentage to obtain a solid mixed salt, which is then placed in a crucible after drying, heated until all melted, and then cooled and ground to obtain a quaternary molten salt;

[0013] B) preparing a carbon-based crystallized product, mixing the quaternary molten salt obtained in step A) with an intermediate and an organic solvent and placing the mixture in a reactor for a stepwise temperature-raising crystallization reaction, and washing the mixture after the stepwise temperature-raising crystallization reaction to obtain a carbon-based crystallized product;

[0014] C) preparing a carbon-based nanomaterial, first drying the carbon-based crystallized product obtained in step B), and then calcining it under a protective atmosphere to obtain a carbon-based nanomaterial;

[0015] D) To prepare the finished product, the carbon-based nanomaterial obtained in step C) is first mixed with a water-soluble phenolic resin and an ethanol solution according to a mass ratio, and then a foaming agent is added and stirred into a slurry, and then granulated to obtain a nanocomposite material for adsorbing inert organic matter.

[0016] In a specific embodiment of the present invention, the ZnCl 2 The mass percentages of LiCl, NaCl and KCl are: ZnCl 2 45-55wt%, LiCl 5-12wt%, NaCl 10-18wt% and KCl 20-35wt%, the blending is physical blending by a mixing device; the drying is vacuum drying and the water content is less than 0.3%; the heating to melting is heating by a vacuum resistance furnace until the solid mixed salt is completely melted; the cooling is natural cooling to room temperature; the grinding refers to grinding the quaternary molten salt that has been melted and naturally cooled to room temperature into powder.

[0017] In another specific embodiment of the present invention, the temperature of the vacuum drying is 80-100°C; the crucible is a porcelain crucible or a graphite crucible; the heating temperature of the resistance furnace heating is 200-240°C, and the heating rate during the resistance furnace heating process is controlled to be 3-6°C / min, and the temperature of the natural cooling to room temperature is 20-30°C; the grinding is performed using a grinder or a mortar.

[0018] In another specific embodiment of the present invention, the process of the step-by-step temperature crystallization reaction in the reactor described in step B) is: first, the quaternary molten salt, the intermediate and the organic solvent are weighed according to the mass ratio, and then the quaternary molten salt and the intermediate are first added to the three-necked flask and the bottle mouth is sealed, and a protective gas is input, and an organic solvent is added under a protective gas atmosphere and mixed uniformly to obtain a solution, and the uniformly mixed solution is transferred to a hydrothermal reactor, and the temperature is stepped and crystallized at a constant temperature under stirring, and the material is discharged after cooling and centrifuged to obtain a crystallized solid after centrifugation, and the crystallized solid is washed 3-5 times with a hydrochloric acid-ethanol mixed solution at room temperature with stirring to obtain a carbon-based crystallized product.

[0019] In another specific embodiment of the present invention, the protective gas is nitrogen; the mass ratio of the quaternary molten salt, the intermediate and the organic solvent is 1:10-15:2-4; the hydrothermal reactor is a hydrothermal reactor with an inner liner, the inner liner is PTFE, the feeding coefficient is less than 0.8 (that is, the ratio of the total weight of the charge in the reactor to the effective volume of the reactor is less than 0.8), the cooling method of the hydrothermal reactor is cooling by passing water or refrigerant, the cooling is to room temperature, the step heating under stirring is heating at a heating rate of 1-3°C / min under a stirring speed of 30-60rpm, and the first stage of the step heating is heated to 160°C, and the second stage is heated to 200°C, the constant temperature crystallization time is 24h in the first stage, and 48-60h in the second stage; the normal temperature stirring and washing is magnetic stirring, and the stirring speed is 400-600rpm.

[0020] In another specific embodiment of the present invention, the intermediate is 1,5-dibromonaphthalene, 1,3,5-tribromobenzene or 1,3,5-triethynylbenzene; the organic solvent is diethylene glycol, cyclopentane sulfone, glycerol, ethylene glycol phenyl ether or propylene carbonate; the hydrochloric acid-ethanol mixed solution is a hydrochloric acid-ethanol mixed solution with a mass percentage concentration of 25-30%, which is prepared by preparing hydrochloric acid with a mass percentage concentration of 37% and anhydrous ethanol with a mass percentage concentration of 99.7%.

[0021] In a more specific embodiment of the present invention, the protective atmosphere in step C) is a nitrogen atmosphere, and the drying is vacuum drying; and a vacuum nitrogen-filled oven is used to dry the mixture at 80-100°C until the moisture content is less than 3%; the roasting is performed in a roasting furnace, and the roasting furnace is a rotary atmosphere furnace, a nitrogen-filled muffle furnace or an electric drum furnace, the roasting time is 240-360 minutes, and the roasting temperature is 580-620°C.

[0022] In a further specific embodiment of the present invention, the carbon-based nanomaterials described in step D) are mixed with the water-soluble phenolic resin and the ethanol solution in a mass ratio of 1:1.5-3:6-10 and stirred evenly, and during the stirring process, the pH value is adjusted to 14 with a liquid alkali having a mass percentage concentration of 20%; the water-soluble phenolic resin is a resol phenolic resin; the mass percentage concentration of the ethanol solution is 40%; the mass percentage of the foaming agent in the mixture of the carbon-based nanomaterials, the water-soluble phenolic resin and the ethanol solution is 5-15%; the liquid alkali is a sodium hydroxide aqueous solution having a mass percentage concentration of 20%.

[0023] In yet another specific embodiment of the present invention, the stirring temperature of adding the foaming agent and stirring into a slurry in step D) is 25°C, the stirring time is 60-180min, the stirring speed is 400-600rpm, the granulation is spray granulation, the device used for spray granulation is a centrifugal spray granulator or a pressure spray granulator, and the inlet temperature of the centrifugal spray granulator or the pressure spray granulator is 260-280°C, the outlet temperature is 160-180°C, and the particle size after spray granulation is 150-200μm.

[0024] In yet another specific embodiment of the present invention, the foaming agent is an organic foaming agent or an inorganic foaming agent, the organic foaming agent is benzenesulfonyl hydrazide, N,N-dinitrosopentamethylenetetramine or urea, and the inorganic foaming agent is ammonium bicarbonate, sodium bicarbonate, ammonium nitrite or ammonium carbonate.

[0025] The technical solution provided by the present invention has the following advantages over the prior art:

[0026] 1). The raw materials are widely available, the process is short, the production cost is reasonable and controllable, and it can meet the requirements of industrial scale-up preparation;

[0027] 2). The quaternary molten salt used as template makes the pore size of the nanomaterial uniform and improves the stability of the product;

[0028] 3). The use of water-soluble phenolic resin for coating and granulation optimizes the compatibility of nanomaterials, which is conducive to significantly improving the adsorption capacity;

[0029] 4). Taking into account the characteristics of high-salt wastewater, the preparation route was innovated to provide technical support for the source utilization of salt resources in mother liquor high-salt wastewater. DETAILED DESCRIPTION

[0030] In order to make the purpose, technical solution and advantages of the present invention more clear, the present invention is further described in detail below. However, it should be understood that the description herein is only used to explain the present invention and is not used to limit the scope of the present invention.

[0031] Unless otherwise defined, all technical terms and scientific terms used herein have the same meanings as those generally understood by those skilled in the art of the present invention. The terms used herein, i.e., in the specification of the present invention, are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The characterization means involved in this article can refer to the relevant descriptions in the prior art and will not be repeated herein.

[0032] The nanocomposite material for adsorbing inert organic matter obtained in the following examples is used for adsorbing inert organic matter in the mother liquor of salt crystallization of high-salt wastewater from a coal chemical industry.

[0033] The main water quality data of the above-mentioned high-salt wastewater salt crystallization mother liquor (i.e. "crystallization mother liquor") are as follows: inert organic matter (inert COD) is 11200 mg / L, TDS is 205600 mg / L, total hardness (in terms of CaCO 3 The content of nitrogen (calculated as SiO2) is 1330 mg / L, potassium ion is 3470 mg / L, nitrate ion is 4730 mg / L, chloride ion is 70840 mg / L, sulfate ion is 49600 mg / L, pH value is 12.7, and total silicon (calculated as SiO2) is 477 mg / L.

[0034] The water quality of the above-mentioned coal chemical wastewater salt crystallization mother liquor is that it contains inert COD, Na + , K + , Ca 2+ Mg 2+ 、NO 3 - , Cl - 、SO 4 2- In order to realize the resource utilization of mother liquor in a multi-component complex system, the key is to remove organic impurities (inert COD).

[0035] Embodiment 1:

[0036] The method for preparing the nanocomposite material for adsorbing inert organic matter provided by the present invention comprises the following steps:

[0037] A) Prepare quaternary molten salt, ZnCl 255% of zinc chloride, 10% of LiCl (lithium chloride), 10% of NaCl (sodium chloride) and 25% of KCl (potassium chloride) are physically blended (i.e., physically mixed) uniformly by a mixing device to obtain a solid mixed salt, and then the solid mixed salt is dried at 100° C. by a vacuum drying device to a moisture content of less than 0.3%, and then placed in a graphite crucible and introduced into a vacuum resistance furnace to be heated to melt at 200° C., that is, the solid mixed salt is heated to be completely melted by the vacuum resistance furnace, and during the heating process, the heating temperature is increased from room temperature to 200° C. at a heating rate of 3° C. / min, and then naturally cooled to 20° C., and then ground by a grinder to obtain a quaternary molten salt, the physical properties of which are powdery;

[0038] B) Preparation of carbon-based crystallized products, firstly weighing the quaternary molten salt obtained in step A) with the intermediate and the organic solvent in a mass percentage of 1:15:2 and mixing them after weighing, and then placing them in a reactor for stepwise temperature rise crystallization reaction, the specific process is: firstly adding the quaternary molten salt and the intermediate into a three-necked flask and sealing the flask mouth, inputting nitrogen as a protective gas, adding the organic solvent under a nitrogen atmosphere (i.e., in a nitrogen atmosphere) and mixing them uniformly to obtain a solution, and then mixing the uniformly mixed flask into a three-necked flask. The obtained solution is transferred to a hydrothermal reactor with a PTFE liner and a feeding coefficient of less than 0.8 (i.e., the ratio of the charging volume of the reactor to the reactor volume is less than 0.8), and the temperature is stepped up and constant temperature crystallization is carried out under the stirring state of the stirring device provided by the hydrothermal reactor. After the constant temperature crystallization is completed, the temperature is lowered, specifically: water or a refrigerant is passed through the jacket of the hydrothermal reactor to lower the temperature, and the refrigerant is such as glycerol, ethylene glycol, ethanol, ice water, liquid nitrogen or liquid oxygen. After the temperature is lowered to room temperature, the material is discharged and Centrifugal separation, after centrifugal separation, a crystallized solid is obtained, and the crystallized solid is stirred and washed three times at room temperature with a hydrochloric acid-ethanol mixed solution with a mass percentage concentration of 25-30% prepared by using hydrochloric acid with a mass percentage concentration of 37% and anhydrous ethanol with a mass percentage concentration of 99.7%, to obtain a carbon-based crystallized product. The step-by-step heating under the stirring state described in this step is: heating at a heating rate of 1°C / min under a stirring speed of 30rpm, and the first stage of the step-by-step heating is heating from room temperature to 160°C, and the second stage is heating from 160°C to 200°C. The constant temperature crystallization time of the first stage, i.e., the constant temperature crystallization time at 160°C, is maintained for 24h, and the constant temperature crystallization time of the second stage, i.e., the constant temperature crystallization time at 200°C, is maintained for 60h. The aforementioned stirring and washing adopts magnetic stirring, and the stirring speed is 500rpm. The intermediate described in this step is 1,5-dibromonaphthalene, and the organic solvent is diethylene glycol;

[0039] C) preparing a carbon-based nanomaterial, first drying the carbon-based crystallized product obtained in step B) in a nitrogen atmosphere with nitrogen as a protective gas in a vacuum nitrogen-filled oven at 90° C. to dry the carbon-based crystallized product to a moisture content of less than 3%, and then sending the carbon-based crystallized product dried to a moisture content of less than 3% to a calcining furnace such as a rotary atmosphere furnace for calcining at 620° C. for 240 min, and taking it out of the furnace after the calcining is completed to obtain a carbon-based nanomaterial, the physical property (morphology) of the carbon-based nanomaterial is powder;

[0040] D) preparing a finished product, which is a nanocomposite material for adsorbing inert organic matter. First, the carbon-based nanomaterial obtained in step C), the resol phenolic resin as a water-soluble phenolic resin and an ethanol solution with a mass percentage concentration of 40% are taken in a mass percentage of 1:1.5:10 and stirred evenly, and during the stirring process, the pH value is adjusted to 14 with a liquid alkali, i.e., a sodium hydroxide (NaOH) aqueous solution with a mass percentage concentration of 20%, and then a foaming agent such as benzenesulfonyl hydrazide is added, which accounts for 5% of the weight of the mixture of the carbon-based material, the water-soluble phenolic resin and the ethanol solution, i.e., the mixed mass of the three. The mixture is stirred at a stirring speed of 600 rpm for 60 minutes, and after being stirred into a slurry, it is introduced into a centrifugal spray granulator for spray granulation, and the particle size after spray granulation is 150 μm, and the inlet temperature of the centrifugal spray granulator is 270° C., and the outlet temperature is 160° C., to obtain a nanocomposite material for adsorbing inert organic matter.

[0041] Embodiment 2:

[0042] The method for preparing the nanocomposite material for adsorbing inert organic matter provided by the present invention comprises the following steps:

[0043] A) Prepare quaternary molten salt, ZnCl 2 45% of zinc chloride, 5% of LiCl (lithium chloride), 15% of NaCl (sodium chloride) and 35% of KCl (potassium chloride) are physically blended (i.e., physically mixed) by a mixing device to obtain a solid mixed salt, and then the solid mixed salt is dried at 80° C. by a vacuum drying device to a moisture content of less than 0.3%, and then placed in a graphite crucible and introduced into a vacuum resistance furnace to be heated to melt at 210° C., that is, the solid mixed salt is heated to be completely melted by a vacuum resistance furnace, and during the heating process, the heating temperature is increased from room temperature to 210° C. at a heating rate of 4° C. / min, and then naturally cooled to 25° C., and then ground by a mortar to obtain a quaternary molten salt, the physical properties of which are powdery;

[0044] B) Preparation of carbon-based crystallized products, firstly weighing the quaternary molten salt obtained in step A) with the intermediate and the organic solvent in a mass percentage of 1:12:4 and mixing them after weighing, and then placing them in a reactor for stepwise temperature rise crystallization reaction, the specific process is: firstly adding the quaternary molten salt and the intermediate into a three-necked flask and sealing the flask mouth, inputting nitrogen as a protective gas, adding the organic solvent under a nitrogen atmosphere (i.e., in a nitrogen atmosphere) and mixing them uniformly to obtain a solution, and then mixing the uniformly mixed The obtained solution is transferred to a hydrothermal reactor with a PTFE liner and a feeding coefficient of less than 0.8 (i.e., the ratio of the charging volume of the reactor to the reactor volume is less than 0.8), and the temperature is stepped up and constant temperature crystallization is carried out under the stirring state of the stirring device provided by the hydrothermal reactor. After the constant temperature crystallization is completed, the temperature is lowered, specifically: water or a refrigerant is passed through the jacket of the hydrothermal reactor to lower the temperature, and the refrigerant is such as glycerol, ethylene glycol, ethanol, ice water, liquid nitrogen or liquid oxygen. After the temperature is lowered to room temperature, the material is discharged and Centrifugal separation, after centrifugal separation, a crystallized solid is obtained, and the crystallized solid is stirred and washed 4 times at room temperature with a hydrochloric acid-ethanol mixed solution with a mass percentage concentration of 25-30% prepared by using hydrochloric acid with a mass percentage concentration of 37% and anhydrous ethanol with a mass percentage concentration of 99.7%, to obtain a carbon-based crystallized product. The step-by-step heating under the stirring state described in this step is: heating at a heating rate of 3°C / min under a stirring speed of 45rpm, and the first stage of the step-by-step heating is from room temperature to 160°C, and the second stage is from 160°C to 200°C. The constant temperature crystallization time of the first stage, i.e., the constant temperature crystallization time at 160°C, is maintained for 24h, and the constant temperature crystallization time of the second stage, i.e., the constant temperature crystallization time at 200°C, is maintained for 55h. The aforementioned stirring and washing adopts magnetic stirring, and the stirring speed is 400rpm. The intermediate described in this step is 1,3,5-tribromobenzene, and the organic solvent is glycerol.

[0045] C) preparing a carbon-based nanomaterial, first drying the carbon-based crystallized product obtained in step B) in a nitrogen atmosphere with nitrogen as a protective gas in a vacuum nitrogen-filled oven at 80° C. to dry the carbon-based crystallized product to a moisture content of less than 3%, and then sending the carbon-based crystallized product dried to a moisture content of less than 3% to a roasting furnace such as a nitrogen-filled muffle furnace and roasting it at 580° C. for 360 minutes, and taking it out of the furnace after the roasting is completed to obtain a carbon-based nanomaterial, the physical property (morphology) of the carbon-based nanomaterial is powder;

[0046] D) preparing a finished product, which is a nanocomposite material for adsorbing inert organic matter. First, the carbon-based nanomaterial obtained in step C), the resol phenolic resin as a water-soluble phenolic resin and an ethanol solution with a mass percentage concentration of 40% are taken in a mass percentage of 1:3:6 and stirred evenly, and during the stirring process, the pH value is adjusted to 14 with a liquid alkali, i.e., a sodium hydroxide (NaOH) aqueous solution with a mass percentage concentration of 20%, and then a foaming agent such as sodium bicarbonate is added, which accounts for 7% of the weight of the mixture of the carbon-based material, the water-soluble phenolic resin and the ethanol solution, i.e., the mixed mass of the three. The mixture is stirred at a stirring speed of 500 rpm for 100 minutes, and after being stirred into a slurry, it is introduced into a centrifugal spray granulator for spray granulation. The particle size after spray granulation is 200 μm, and the inlet temperature of the centrifugal spray granulator is 280° C., and the outlet temperature is 180° C., to obtain a nanocomposite material for adsorbing inert organic matter.

[0047] Embodiment 3:

[0048] The method for preparing the nanocomposite material for adsorbing inert organic matter provided by the present invention comprises the following steps:

[0049] A) Prepare quaternary molten salt, ZnCl 2 50% zinc chloride, 12% LiCl (lithium chloride), 18% NaCl (sodium chloride) and 20% KCl (potassium chloride) are physically blended (i.e., physically mixed) uniformly by a mixing device to obtain a solid mixed salt, and then the solid mixed salt is dried at 90° C. by a vacuum drying device to a moisture content of less than 0.3%, and then placed in a porcelain crucible and introduced into a vacuum resistance furnace to be heated to melt at 225° C., that is, the solid mixed salt is heated to be completely melted by a vacuum resistance furnace, and during the heating process, the heating temperature is increased from room temperature to 225° C. at a heating rate of 6° C. / min, and then naturally cooled to 30° C., and then ground by a mortar to obtain a quaternary molten salt, the physical properties of which are powdery;

[0050] B) Preparation of carbon-based crystallized products, firstly weighing the quaternary molten salt obtained in step A) with the intermediate and the organic solvent in a mass percentage of 1:10:3 and mixing them after weighing, and then placing them in a reactor for stepwise temperature rise crystallization reaction, the specific process is: firstly adding the quaternary molten salt and the intermediate into a three-necked flask and sealing the flask mouth, inputting nitrogen as a protective gas, adding the organic solvent under a nitrogen atmosphere (i.e., in a nitrogen atmosphere) and mixing them uniformly to obtain a solution, and then placing the uniformly mixed solution into a reactor. The obtained solution is transferred to a hydrothermal reactor with a PTFE liner and a feeding coefficient of less than 0.8 (i.e., the ratio of the charging volume of the reactor to the reactor volume is less than 0.8), and the temperature is stepped up and constant temperature crystallization is performed under the stirring state of the stirring device provided by the hydrothermal reactor. After the constant temperature crystallization is completed, the temperature is lowered, specifically: water or a refrigerant is passed through the jacket of the hydrothermal reactor to lower the temperature, and the refrigerant is such as glycerol, ethylene glycol, ethanol, ice water, liquid nitrogen or liquid oxygen. After the temperature is lowered to room temperature, the material is discharged and centrifuged. Separation, after centrifugal separation, a crystallized solid is obtained, and the crystallized fixed material is stirred and washed 5 times at room temperature with a hydrochloric acid ethanol mixed solution with a mass percentage concentration of 25-30% prepared by hydrochloric acid with a mass percentage concentration of 37% and anhydrous ethanol with a mass percentage concentration of 99.7%, to obtain a carbon-based crystallized material. The step-by-step heating under the stirring state described in this step is: heating at a heating rate of 2°C / min under a stirring speed of 60rpm, and the first stage of the step-by-step heating is from room temperature to 160°C, and the second stage is from 160°C to 200°C. The constant temperature crystallization time of the first stage, that is, the constant temperature crystallization time at 160°C, is maintained for 24h, and the constant temperature crystallization time of the second stage, that is, the constant temperature crystallization time at 200°C, is maintained for 52h. The aforementioned stirring and washing adopts magnetic stirring, and the stirring speed is 550rpm. The intermediate described in this step is 1,3,5-triethynylbenzene, and the organic solvent is ethylene glycol phenyl ether;

[0051] C) preparing carbon-based nanomaterials, first drying the carbon-based crystallized product obtained in step B) in a nitrogen atmosphere with nitrogen as a protective gas in a vacuum nitrogen-filled oven at 95° C. to dry the carbon-based crystallized product to a moisture content of less than 3%, and then sending the carbon-based crystallized product dried to a moisture content of less than 3% to a roasting furnace such as an electric drum furnace for roasting at 600° C. for 320 min, and taking it out of the furnace after the roasting is completed to obtain a carbon-based nanomaterial, the physical property (morphology) of the carbon-based nanomaterial is powder;

[0052] D). preparing a finished product, which is a nanocomposite material for adsorbing inert organic matter, firstly, the carbon-based nanomaterial obtained in step C), the resol phenolic resin as a water-soluble phenolic resin and the ethanol solution with a mass percentage concentration of 40% are taken in a mass percentage of 1:2:8 and stirred evenly, and during the stirring process, the pH value is adjusted to 14 with liquid alkali, i.e., a sodium hydroxide (NaOH) aqueous solution with a mass percentage concentration of 20%, and then a foaming agent such as N,N-dinitrosopentamethylenetetramine is added, which accounts for 12% of the weight of the mixture of the carbon-based material, the water-soluble phenolic resin and the ethanol solution, i.e., the mixed mass of the three, and stirred at a stirring speed of 400 rpm for 180 minutes. After being stirred into a slurry, it is introduced into a pressure spray granulator for spray granulation, and the particle size after spray granulation is 180 μm, and the inlet temperature of the pressure spray granulator is 272° C., and the outlet temperature is 170° C., so as to obtain a nanocomposite material for adsorbing inert organic matter.

[0053] Embodiment 4:

[0054] The method for preparing the nanocomposite material for adsorbing inert organic matter provided by the present invention comprises the following steps:

[0055] A) Prepare quaternary molten salt, ZnCl 2 46% of zinc chloride, 7% of LiCl (lithium chloride), 17% of NaCl (sodium chloride) and 30% of KCl (potassium chloride) are physically blended (i.e., physically mixed) by a mixing device to obtain a solid mixed salt, and then the solid mixed salt is dried at 95° C. by a vacuum drying device to a moisture content of less than 0.3%, and then placed in a porcelain crucible and introduced into a vacuum resistance furnace to be heated to melt at 240° C., that is, the solid mixed salt is heated to be completely melted by the vacuum resistance furnace, and during the heating process, the heating temperature is increased from room temperature to 240° C. at a heating rate of 5° C. / min, and then naturally cooled to 22° C., and then ground by a grinder to obtain a quaternary molten salt, the physical properties of which are powdery;

[0056] B) Preparation of carbon-based crystallized products, firstly weighing the quaternary molten salt obtained in step A) with the intermediate and the organic solvent in a mass percentage of 1:14:2.5 and mixing them after weighing, and then placing them in a reactor for stepwise temperature rise crystallization reaction, the specific process is: firstly adding the quaternary molten salt and the intermediate into a three-necked flask and sealing the flask mouth, inputting nitrogen as a protective gas, adding the organic solvent under a nitrogen atmosphere (i.e., in a nitrogen atmosphere) and mixing them uniformly to obtain a solution, and uniformly The mixed solution is transferred to a hydrothermal reactor with a PTFE liner and a feeding coefficient of less than 0.8 (i.e., the ratio of the charging volume of the reactor to the reactor volume is less than 0.8), and the temperature is stepped up and constant temperature crystallization is performed under the stirring state of the stirring device provided by the hydrothermal reactor. After the constant temperature crystallization is completed, the temperature is lowered, specifically: water or a refrigerant is passed through the jacket of the hydrothermal reactor to lower the temperature, and the refrigerant is, for example, glycerol, ethylene glycol, ethanol, ice water, liquid nitrogen or liquid oxygen. After the temperature is lowered to room temperature, the material is discharged. and centrifugation to obtain a crystallized solid after centrifugation, and the crystallized solid is stirred and washed 5 times at room temperature with a hydrochloric acid-ethanol mixed solution with a mass percentage concentration of 25-30% prepared by hydrochloric acid with a mass percentage concentration of 37% and anhydrous ethanol with a mass percentage concentration of 99.7%, to obtain a carbon-based crystallized product, the step-by-step heating under the stirring state described in this step is: heating at a heating rate of 3°C / min under a stirring speed of 50rpm, and the first stage of the step-by-step heating is from room temperature to 160°C, and the second stage is from 160°C to 200°C, the constant temperature crystallization time of the first stage, that is, the constant temperature crystallization time at 160°C, is maintained for 24h, and the constant temperature crystallization time of the second stage, that is, the constant temperature crystallization time at 200°C, is maintained for 48h, the aforementioned stirring and washing is magnetic stirring, and the stirring speed is 600rpm, the intermediate described in this step is 1,5-dibromonaphthalene, and the organic solvent is cyclopentane sulfone;

[0057] C) preparing a carbon-based nanomaterial, first drying the carbon-based crystallized product obtained in step B) in a nitrogen atmosphere with nitrogen as a protective gas in a vacuum nitrogen-filled oven at 100° C. to dry the carbon-based crystallized product to a moisture content of less than 3%, and then sending the carbon-based crystallized product dried to a moisture content of less than 3% to a calcining furnace such as a nitrogen-filled muffle furnace and calcining it at 590° C. for 340 minutes, and taking it out of the furnace after the calcining is completed to obtain a carbon-based nanomaterial, the physical property (morphology) of the carbon-based nanomaterial is powder;

[0058] D) preparing a finished product, which is a nanocomposite material for adsorbing inert organic matter. First, the carbon-based nanomaterial obtained in step C), the resol phenolic resin as a water-soluble phenolic resin and an ethanol solution with a mass percentage concentration of 40% are taken in a mass percentage of 1:2.5:7 and stirred evenly, and during the stirring process, the pH value is adjusted to 14 with a liquid alkali, i.e., a sodium hydroxide (NaOH) aqueous solution with a mass percentage concentration of 20%, and then a foaming agent such as ammonium bicarbonate is added, which accounts for 15% of the weight of the mixture of the carbon-based material, the water-soluble phenolic resin and the ethanol solution, i.e., the mixed mass of the three. The mixture is stirred at a stirring speed of 550 rpm for 90 minutes, and after being stirred into a slurry, it is introduced into a centrifugal spray granulator for spray granulation. The particle size after spray granulation is 160 μm, and the inlet temperature of the centrifugal spray granulator is 276° C., and the outlet temperature is 175° C., to obtain a nanocomposite material for adsorbing inert organic matter.

[0059] The nanocomposite materials for adsorbing inert organic matter prepared by the above-mentioned Examples 1 to 4 have the technical effects shown in the following table on the treatment of the above-mentioned mother liquor of desalination and crystallization of high-salt wastewater from a certain coal chemical industry.

[0060]

[0061] The above is only a preferred embodiment of the present invention. It should be pointed out that for those skilled in the art, several improvements and modifications can be made without departing from the technical essence of the present invention. These improvements and modifications should also be regarded as within the scope of protection of the present invention.

Claims

1. A method for preparing a nanocomposite material for adsorbing inert organic matter, characterized in that: The following steps are involved: A) Preparation of quaternary molten salt: firstly, ZnCl2, LiCl, NaCl and KCl are mixed according to weight percentage to obtain a solid mixed salt, and then placed in a crucible after drying, heated until all melted, and then cooled and ground to obtain a quaternary molten salt; B) preparing a carbon-based crystallized product, mixing the quaternary molten salt obtained in step A) with an intermediate and an organic solvent and placing the mixture in a reactor for a stepwise temperature-raising crystallization reaction, and washing the mixture after the stepwise temperature-raising crystallization reaction to obtain a carbon-based crystallized product; C) preparing a carbon-based nanomaterial, first drying the carbon-based crystallized product obtained in step B), and then calcining it under a protective atmosphere to obtain a carbon-based nanomaterial; D) To prepare the finished product, the carbon-based nanomaterial obtained in step C) is first mixed with a water-soluble phenolic resin and an ethanol solution according to a mass ratio, and then a foaming agent is added and stirred into a slurry, and then granulated to obtain a nanocomposite material for adsorbing inert organic matter.

2. The method for preparing a nanocomposite material for adsorbing inert organic matter according to claim 1, characterized in that: The mass percentages of ZnCl2, LiCl, NaCl and KCl in step A) are: ZnCl2 45-55wt%, LiCl 5-12wt%, NaCl 10-18wt% and KCl 20-35wt%, the blending is physical blending using a mixing device; the drying is vacuum drying and the vacuum drying is performed until the moisture content is less than 0.3%; the heating to melting is heating to completely melt the solid mixed salt using a vacuum resistance furnace; the cooling is natural cooling to room temperature; the grinding refers to grinding the quaternary molten salt that has been melted and naturally cooled to room temperature into powder.

3. The method for preparing a nanocomposite material for adsorbing inert organic matter according to claim 2, characterized in that: The temperature of the vacuum drying is 80-100°C; the crucible is a porcelain crucible or a graphite crucible; the heating temperature of the resistance furnace heating is 200-240°C, and the heating rate during the resistance furnace heating process is controlled to be 3-6°C / min, and the temperature of the natural cooling to room temperature is 20-30°C; the grinding is performed using a grinder or a mortar.

4. The method for preparing a nanocomposite material capable of absorbing inert organic matter according to claim 1, characterized in that: The process of the step-by-step temperature crystallization reaction in the reactor described in step B) is: first weigh the quaternary molten salt, the intermediate and the organic solvent according to the mass ratio, then first add the quaternary molten salt and the intermediate into the three-necked flask and seal the bottle mouth, input the protective gas, add the organic solvent under the protective gas atmosphere and mix uniformly to obtain a solution, and transfer the uniformly mixed solution to the hydrothermal reactor, stepwise increase the temperature and crystallize at a constant temperature under stirring, discharge the material after cooling and centrifuge, obtain a crystallized solid after centrifugation, and wash the crystallized solid with a hydrochloric acid-ethanol mixed solution at room temperature for 3-5 times to obtain a carbon-based crystallized product.

5. The method for preparing a nanocomposite material capable of absorbing inert organic matter according to claim 4, characterized in that: The protective gas is nitrogen; the mass ratio of the quaternary molten salt, the intermediate and the organic solvent is 1:10-15:2-4; the hydrothermal reactor is a hydrothermal reactor with an inner lining, the inner lining is PTFE, the feeding coefficient is less than 0.8, the cooling method of the hydrothermal reactor is cooling by passing water or refrigerant, the cooling is to room temperature, the step heating under stirring is heating at a heating rate of 1-3°C / min under a stirring speed of 30-60rpm, and the first stage of the step heating is heated to 160°C, and the second stage is heated to 200°C, the constant temperature crystallization time is 24h in the first stage, and 48-60h in the second stage; the normal temperature stirring and washing is magnetic stirring, and the stirring speed is 400-600rpm.

6. The method for preparing a nanocomposite material capable of absorbing inert organic matter according to claim 5, characterized in that: The intermediate is 1,5-dibromonaphthalene, 1,3,5-tribromobenzene or 1,3,5-triethynylbenzene; the organic solvent is diethylene glycol, cyclopentane sulfone, glycerol, ethylene glycol phenyl ether or propylene carbonate; the hydrochloric acid-ethanol mixed solution is a hydrochloric acid-ethanol mixed solution with a mass percentage concentration of 25-30%, which is prepared by preparing hydrochloric acid with a mass percentage concentration of 37% and anhydrous ethanol with a mass percentage concentration of 99.7%.

7. The method for preparing a nanocomposite material capable of absorbing inert organic matter according to claim 1, characterized in that: The protective atmosphere in step C) is a nitrogen atmosphere, and the drying is vacuum drying; and a vacuum nitrogen-filled oven is used to dry the mixture at 80-100° C. until the moisture content is less than 3%; the roasting is carried out in a roasting furnace, and the roasting furnace is a rotary atmosphere furnace, a nitrogen-filled muffle furnace or an electric drum furnace, and the roasting time is 240-360 minutes and the roasting temperature is 580-620° C.

8. The method for preparing a nanocomposite material capable of absorbing inert organic matter according to claim 1, characterized in that: The carbon-based nanomaterial, the water-soluble phenolic resin and the ethanol solution described in step D) are mixed in a mass ratio of 1:1.5-3:6-10 and stirred evenly, and during the stirring process, the pH value is adjusted to 14 with a liquid alkali with a mass percentage concentration of 20%; the water-soluble phenolic resin is a resol phenolic resin; the mass percentage concentration of the ethanol solution is 40%; the mass percentage of the foaming agent in the mixture of the carbon-based nanomaterial, the water-soluble phenolic resin and the ethanol solution is 5-15%; the liquid alkali is a sodium hydroxide aqueous solution with a mass percentage concentration of 20%.

9. The method for preparing a nanocomposite material capable of absorbing inert organic matter according to claim 1, characterized in that: The stirring temperature of adding the foaming agent and stirring into a slurry in step D) is 25° C., the stirring time is 60-180 min, the stirring speed is 400-600 rpm, the granulation is spray granulation, the device used for spray granulation is a centrifugal spray granulator or a pressure spray granulator, and the inlet temperature of the centrifugal spray granulator or the pressure spray granulator is 260-280° C., the outlet temperature is 160-180° C., and the particle size after spray granulation is 150-200 μm.

10. The method for preparing a nanocomposite material capable of absorbing inert organic matter according to claim 8 or 9, characterized in that: The foaming agent is an organic foaming agent or an inorganic foaming agent. The organic foaming agent is benzenesulfonyl hydrazide, N,N-dinitrosopentamethylenetetramine or urea. The inorganic foaming agent is ammonium bicarbonate, sodium bicarbonate, ammonium nitrite or ammonium carbonate.